Emotional labor : the invisible work shaping our lives and how to claim our power - Hackman, Rose (Flatiron Books, 2023)
"A scathing, deeply-researched foray into the invisible, uncompensated work women perform every day 'Emotional labor.' The term might sound familiar. . .but what does it mean exactly? Initially used to describe the unnamed yet crucial labor flight attendants did to make guests feel welcomed and safe, the phrase has burst into the national lexicon in recent years. The examples, whispered among friends and posted online, are endless. A woman is tasked with organizing family functions, even without volunteering. A stranger insists you 'smile more,' even as you navigate a high stress environment or grating commute. Emotional labor is essential to our society and economy, but it's so often invisible. Many are asked to perform exhausting, draining work at no extra cost. In this groundbreaking, journalistic deep dive, Rose Hackman traces the history of the term and exposes common manifestations of the phenomenon. She describes the many ways women and girls are forced to edit the expressions of their emotions to accommodate and elevate the emotions of others. But Hackman doesn't simply diagnose a problem-she empowers us to combat patriarchy and forge pathways for radical evolution, justice, and change. The 2023 must-have for every reader"--Provided by publisher.